Etapas de desarrollo de la planta de frijol comun (Phaseolus vulgaris L.) - Fernández de Córdova, F.; Gepts, Paul L.; López, M. (International Center for Tropical Agriculture, 1986)
A development scale of the common bean plant, designed by CIAT, is presented in order to provide bean researchers and technicians with a standard and stable pattern to which observations and practices can be referred to. The scale is numeric and is based on the morphological characteristics that the plant exhibits according to a given physiological stage. Color photos of the plant in the different developmental stages are provided. (CIAT)